MINUSTAH e diplomacia solidária : criação de um novo paradigma nas operações de paz? - Correa, Paulo Gustavo Pellegrino (Universidade Federal de São Carlos, 2009)
The purpose of our research is to test the Brazilian proposal of creating a new paradigm of intrastate conflict resolution from its experience in the command of United Nations Stabilization Mission in Haiti ( MINUSTAH ). The Brazilian motivations in joining the rebuilding process of Haiti ( Solidarity Diplomacy ) and a multidimensional vision are aspects that, according to the Brazilian government, would distinguish MINUSTAH from past unsuccessful missions commanded by the United States. First of all, we ll analyze the political/ ideological motivations of the peacekeeping operation contributors, more specifically the USA and Brazil. Then, we will evaluate any innovative aspect in Brazil s cooperation projects carried out by Brazilian Agency for Cooperation (ABC) provided to Haiti and we ll compare them to the projects developed by the United States Agency for International Development (USAID) concerning the projects formulation process and objectives. At last, we'll analyze MINUSTAH s modus operandis, more specifically the Brazilian troops, to be able to check if, in fact, there is a Brazilian ethos capable of supporting a change of paradigm in the peacekeeping operations.
Keywords: Política internacional; Nações Unidas; Paz; Brasil - intervenção militar; Haiti; CIENCIAS HUMANAS::CIENCIA POLITICA